2020
DOI: 10.1002/adhm.201900750
|View full text |Cite
|
Sign up to set email alerts
|

Second Generation Nanoporous Silicon Nitride Membranes for High Toxin Clearance and Small Format Hemodialysis

Abstract: Conventional hemodialysis (HD) uses floor‐standing instruments and bulky dialysis cartridges containing ≈2 m2 of 10 micrometer thick, tortuous‐path membranes. Portable and wearable HD systems can improve outcomes for patients with end‐stage renal disease by facilitating more frequent, longer dialysis at home, providing more physiological toxin clearance. Developing devices with these benefits requires highly efficient membranes to clear clinically relevant toxins in small formats. Here, the ability of ultrathi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…[22] Perfusion rates in our microfluidic devices were adjusted to 1 mL min −1 , as shown by others not to affect systolic blood pressure or heartbeat rate in rats. [19,23] Results with murine blood indicated that E. coli-activated macrophage membrane-coated SiNW adsorbent surfaces are more effective for extracorporeal cleansing of blood in a microfluidic device than commercially available hemofiltration membranes. Importantly, cleansing of blood from healthy human donors using macrophage membrane-coated adsorbent surfaces does not affect healthy cytokine levels.…”
Section: Discussionmentioning
confidence: 99%
“…[22] Perfusion rates in our microfluidic devices were adjusted to 1 mL min −1 , as shown by others not to affect systolic blood pressure or heartbeat rate in rats. [19,23] Results with murine blood indicated that E. coli-activated macrophage membrane-coated SiNW adsorbent surfaces are more effective for extracorporeal cleansing of blood in a microfluidic device than commercially available hemofiltration membranes. Importantly, cleansing of blood from healthy human donors using macrophage membrane-coated adsorbent surfaces does not affect healthy cytokine levels.…”
Section: Discussionmentioning
confidence: 99%
“…The ultrathin nanoporous membranes can be molecularly thin (B10 nm in thickness) and, subsequently, much more permeable than traditional nanoporous membranes but still robust enough to be self-standing in the solution. 71 The ultrathin nanoporous membranes can be considered as superior alternatives for hemodialysis 72 and cell co-culture 73 and also as enabling nanomaterials for wearable artificial kidney 74 and tissue-on-chips. 75 The dimensions of ultrathin solid-state nanopore membranes can be similar to those of the nuclear envelope perforated by nuclear pore complexes with a pore length of 35 nm and a pore radius of 24 nm.…”
Section: Solid-state Nanopore Membranementioning
confidence: 99%
“…Moreover, membranes should be ultrathin to guarantee a large surface area in a small device and should have sufficient strength and appropriate pore sizes to allow middle molecular weight molecules' removal. This might be offered by nanoporous siliconnitride-based membranes, with a diameter of pores typically 100 nanometers or smaller [9]. Novel membranes that contain mesoporous carbons, i.e., nanoporous material containing pores with diameters between 2 and 50 nm, as sorbents with dual-porosity (micro/meso) or sorbent particles for selective and efficient removal of protein-bound uremic toxins as well as cytokines from human plasma, may provide promising alternatives [10][11][12].…”
Section: Dialysis Technology Advancements To Enhance Toxin Removalmentioning
confidence: 99%